THE EFFECTIVENESS OF SOY MILK TO OVERCOME POLIMENOREA IN PREMENOPAUSAL WOMEN IN THE TELUK BAYUR HEALTH CENTER WORK AREA 2022 - Fatmawati Fatmawati; Dwi Hartati (Media Bina Ilmiah, 2023)
Background: Low-dose hormon therapy using natural ingredients called phytoestrogens such as soy milk is a way to overcome or reduce classic symptoms of perimenopause such as menstrual disorders polymenorrhea. Data from the Puskesmas and Posbindu in the Teluk Bayur area, there were 68 women aged 40 years and over who complained of irregular menstruation with elderly people ranging from 40-55 years. Objective: To analyze the effectiveness of soy milk to treat polymenorrhea in peri-menopausal women in the working area of Teluk Bayur Health Center, Berau District. Method: The research design used is a quantitative approach with the praw experiment method. This one group pretest-posttest design consists of one predetermined group. The sample is peri-menopausal women in the working area of the Teluk Bayur Health Center, totaling 23 people. Data analysis used the wilcoxon test. Results: The intensity of polimenorea before giving soy milk to peri-menopausal women was found to be entirely abnormal (polimenorea) totaling 23 people (100%), whereas after giving soy milk to peri-menopausal women most were normal (not polimenorea) totaling 17 people (73 ,9%). Soy milk is effective for treating polymenorrhea in peri-menopausal women in the working area of the Teluk Bayur Health Center, Berau Regency (p value obtained 0.000 <0.05). Conclusion: soy milk is effective for treating polymenorrhea in peri-menopausal women in the working area of the Teluk Bayur Health Center, Berau Regency Keywords: Soy Milk, Polimenorea, Peri-Menapause